Determinants of unemployment among fresh graduates in Malaysia before and during Covid-19 pandemic - Heng, Han Quan; Lim, Chan Hong; Wee, Theo Daniel Xin Lik; Yep, Zhen Yi (2023)
In this research, the primary focus is to examine the factors that contribute to the fresh graduate unemployment in Malaysia. The independent variables included are employability skills (ES), job mismatch (JM), graduates’ attributes (GA), and economic instability (EI) and fresh graduate unemployment in Malaysia being our dependent variable. In addition, some theories such as Human Capital Theory and Job Matching Theory are found to be useful towards this study. The targeted respondents in this study are fresh graduates who ages between 20 to 30 in Malaysia. This study collected two sets data from questionnaire with DV1 (duration of unemployment among fresh graduates in Malaysia before Covid-19 pandemic) and DV2 (duration of unemployment among fresh graduates in Malaysia during Covid-19 pandemic), following to independent variables, including ES, JM, GA, and EI. The data analysis of this study is conducted in SPSS, descriptive and inferential analysis including demographic analysis, reliability analysis, multiple regression analysis, etc are conducted to determine the relationship between the independent variable and the dependent variable. This study has proven that all the independent variables introduced, ES, JM, GA, and EI have proven to be significant when regressing with the dependent variable DV1 and DV2 in multiple linear regression. The ES is most significant for DV1 while the EI is most significant for DV2. It illustrates that the respondents changed their views on fresh graduates’ unemployment due to Covid-19 pandemic outbreak. In addition, the researchers found that there are significant mean differences in ES, GA, and EI while there is no significant mean difference in JM.